PENGARUH BRAND IMAGE DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI KONSUMEN PADA PRODUK MOBIL TOYOTA ETIOS VALCO (Studi Pada PT. Agung Automall Pekanbaru) - ", Antoni; Herianto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the higher level of competition, companies must be able to face competitors offering similar products. Competition between brands of each product in the vehicle will be more sharply captured the interest and attention of consumers. Realizing that the company PT. Agung Automall have prepared themselves by offering after-sales services that include maintenance and repair and supply of spare parts for the Toyota customer partners.This study aims to identify and analyze the brand image and brand trust car Etios Valco, and to determine the interest in buying the car Etios Valco and to investigate the influence of brand image and brand trust towards buying interest car Etios Valco at PT. Agung Automall Pekanbaru. This research is descriptive quantitative statistical calculations. The statistical analysis used in this research is multiple linear regression. The population in this study is the partner of customers in 2015 at PT. Agung Automall as many as 40 people. While the sampling technique uses accidental sampling method, ie the sampling technique based on chance.The results showed that the respondents said "agree" the brand image of Toyota is perceived by the consumer is a brand that is highly qualified and respondents said "strongly agree" to trust the brand Toyota is perceived by consumers is very high, as well as the respondents said "agree" interest in buying products car toyota perceived by consumers is very high. Brand image and brand trust significantly influence buying interest car Etios Valco at PT. Agung Automall Pekanbaru. This is evidenced by F count variable brand image and brand trust by (12.243) greater than> F table (3.355) and Sig. (0,000) <0.05. Meaning is the brand image and brand trust simultaneous influence on consumer buying interest car Etios Valco at PT. Agung Automall Pekanbaru Branch has been verified.Keywords: Brand Image, Brand Trust, Interests Buy Consumer